Clinical application and outcomes of reconstructive microsurgery in Africa: A systematic review and meta-analysis. Issue 7 (July 2022) - Banda, Chihena H; Wilson, Emma; Malata, Charles M.; Narushima, Mitsunaga; Ogawa, Tomoko; Hassanein, Zeinab M; Shiraishi, Makoto; Okada, Yoshimoto; Ghorra, Dina T.; Ishiura, Ryohei; Danno, Kanako; Mitsui, Kohei; et al.
Abstract: Background: Reconstructive microsurgical free flap techniques are often the treatment of choice for a variety of complex tissue defects across multiple surgical specialties. However, the practice is underdeveloped in low- and middle-income countries. The aim of this systematic review was to evaluate the clinical application and outcomes of reconstructive microsurgery performed in Africa. Methods: Seven databases (PubMed, Web of Science, MEDLINE, CINAHL, Academic Search Complete, Embase, and Google Scholar) were searched for studies reporting microsurgical procedures performed in Africa. The risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Tools and quality of evidence using the GRADE approach. Meta-analysis was performed using a random effects model to estimate the pooled proportion of events with 95% confidence intervals. The primary outcome was free flap success rate, and the secondary outcomes were the complication and flap salvage rates. Results: Ninety-two studies were included in the narrative synthesis and nine in the pooled meta-analysis. In total, 1376 free flaps in 1327 patients from 1976 to 2020 were analyzed. Head and neck oncologic reconstruction made up 30% of cases, while breast reconstruction comprised 2%. The pooled flap survival rate was 89% (95% CI: 0.84, 0.93), complication rate 51% (95% CI: 0.36, 0.65), and free flap salvage rate was 45% (95% CI: 0.08, 0.84). Conclusion: This meta-analysis showed that the free flap success rates in Africa are high and comparable to those reported in high-income countries. However, the comparatively higher complication rate and lower salvage rate suggest a need for improved perioperative care. Review registration: Registered with the International Prospective Register of Systematic Reviews (PROSPERO) on 25th September 2020, ID: CRD42020192344. Graphical abstract: Image, graphical abstract